The Native, Naturalized and Adventicies Euphorbiaceae Jus. of La Pampa, Argentine (Semiárida, 2020)
In this contribution the whole genera and species of the Euphorbiaceae family which grows spontaneously in the Province of La Pampa, Argentine, are listed. This family is represented by 8 genera with 23 species. Keys for the identification of the genera and species are included. A short description, distribution, origin and diffusion in La Pampa of each species are given and 18 species are illustrated.